Hepatoprotective Effect of Ethanolic Extract of Rosemarinus officinalis (Rosemary) Leaves Against CCL4-induced Hepatic Damage in Albino Rats (Journal of Environmental Bioremediation and Toxicology, 2024)
The aromatic herb Rosmarinus officinalis L. (Rosemary) is from the Lamiaceae family and has been traditionally used in culinary and folk medicine for various ailments, including liver disorders. In this study, we evaluated the hepatoprotective and nephroprotective effects of the ethanolic leaf extract of Rosmarinus officinalis against carbon tetrachloride (CCl4)-induced toxicity in albino rats. Rats were administered 0.5 mL/kg b.w. of CCl4 intraperitoneally and subsequently orally treated with either 200 or 400 mg/kg b.w. of rosemary extract for four weeks. The standard group received silymarin at 100 mg/kg body weight. The serum levels of biomarkers, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), electrolytes, urea, and creatinine, were then evaluated. Phytochemical screening results indicated the presence of alkaloids, flavonoids, tannins, steroids, phenols, and terpenes in the extract. Our results show that treatment with rosemary extract significantly (p
Keywords: Rosmarinus officinalis; Carbon tetrachloride toxicity; Hepatoprotective and nephroprotective effects; Ethanolic leaf extract; Oxidative stress biomarkers